Colored Women Beauty Rebellion in the 21th century. Celebrating Dark Skin Beauty in Maya Angelou's "Phenomenal Woman"1995 - BENMAGHNIA, KAMAR (My University, 2020)
This research is a chronological order of all the events which marked all the huge steps of colored women in the beauty and fashion field. From being ignored due to their physical appearance and skin color in the fashion industry Their struggles in finding the right cosmetics as the perfect foundation shade for their skin tone or the right hair conditioner and how they rebelled and sparked a spot for their own in the beauty industry for their own cosmetics products. This dissertation holds a new term of “black face fishing” which determine a new phenomenal faced by black women in the beauty industry and how they react to it in social media. Social media plays a huge role in manipulating people’s minds on beauty standards and how some beauty experts use black women features to create a new version of mixed descent beauty the “ Black Barbie” which many colored women don’t appreciate and rebel against it .The rebellion of African American women in many domains including the beauty field has went beyond viral into creating real businesses and owning brands, which turned them into billionaires in the United States of America and sparked a whole flame in the feminist and right activists world in supporting black women movements and paths to success and being an inspiration to all women from different ethnic groups. I finally rely all my research point of views on a unique work of art, a masterpiece written by a famous right women movement activist, a poet, a true diva Maya Angelou whose poem “Phenomenal woman” celebrates female power.
Keywords: Colored Women; Female power; Beauty; Cosmetics